Hubungan Ketersediaan Pangan Dan Hygiene Sanitasi Terhadap Kejadian Stunting Pada Anak Usia 24-59 Bulan di Wilayah Kerja Puskesmas Ulu Moro’o - Agnes Sry Vera Nababan; Athira Demitri; Eka Nenni Jairani; Yulita Yulita; Yemima Gulo (STIKES Columbia Asia Medan, 2024)
. Stunting is a condition of children with a length or height that is less different from children of the same age. Stunting is also a growth and development disorder caused by a lack of nutritional intake, where the results of measuring the nutritional status of children based on the PB / U or TB / U category are at the z-score threshold of -2 SD to -3 SD. The purpose of this study was to determine the relationship between food availability and sanitation hygiene to the incidence of stunting in children aged 24-59 months in the Ulu Moro'o Health Center working area. This type of research is quantitative using analytical observational methods with a cross sectional approach and data analyzed using the Chi Square test. The population of this study were children aged 24-59 months in the Ulu Moro'o Health Center working area, namely 136 children. The sampling technique used simple random sampling of 101 children. Food availability for stunting with a value of p = 0.000 <0.05. Sanitary hygiene against stunting events with a value of p = 0.000 <0.05. There is a relationship between food availability and stunting. There is a relationship between sanitary hygiene and the incidence of stunting in the work area of the Ulu Moro'o Health Center. It is expected that mothers of children aged 24-59 months can meet the availability of food every day so that children can consume nutritious and balanced foods to meet their intake.